Social Movement Studies in Europe : the State of the Art - Fillieule, Olivier; Accornero, Guya (Protest, Culture & Society., 2016)
Bringing together over forty established and emerging scholars, this landmark volume is the first to comprehensively examine the evolution and current practice of social movement studies in a specifically European context. While its first half offers comparative approaches to an array of significant issues and movements, its second half assembles focused national studies that include most major European states. Throughout, these contributions are guided by a shared set of historical and social-scientific questions with a particular emphasis on political sociology, thus offering a bold and uncommonly unified survey that will be essential for scholars and students of European social movements.